SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA BIDIKMISI MENGGUNAKAN METODE SAW (STUDI KASUS : BAG. KEMAHASISWAAN UNIVERSITAS VICTORY SORONG) - Juneth Nelfia Wattimena; Dami Siro Urbasa; Peter Manuputty (LPPM Poltek ST Paul, 2020)
Bidikmisi Scholarship is the education expense assistance program of Indonesian government through the higher education general directorate, ministry of education and culture for the students candidate who do not have economy inadequate and have academic potential to pursue the education in college on a leading study program until graduation on time. The target of Bidikmisi Scholarship program is the graduate of high school education unit or another equivalent that is economically inadequate but has good academic potential. Victory University of Sorong also receives Bidikmisi Scholarship that comes from various sources, but the selection system for the receiver of Bidikmisi Scholarship is not completely computerized, it still uses Microsoft Office Excel. For maximizing the system of giving the scholarship for the students opportunely, then it needs to be applied The Support System for Acquisition Decision of Bidikmisi Scholarship Using SAW Method (Study Case: Student Affairs Part of Victory University in Sorong) so that it can help speed up and make it easier the scholarship giving in making an accurate decision for worthy or failing student to accept the scholarship.